Prenatal internalizing symptoms as a mediator linking maternal adverse childhood experiences with infant temperament. (May 2022) - Mattera, Jennifer A.; Waters, Sara F.; Lee, SuYeon; Connolly, Christopher P.; Gartstein, Maria A.
Abstract: Background: Maternal adverse childhood experiences are known to significantly influence offspring development. However, mediators linking maternal early-life adversity with infant temperament remain largely unknown. Aims: The current study investigated whether prenatal internalizing symptoms mediate the association between maternal adverse childhood experiences and infant temperament at two months. Maternal sensitivity/responsiveness during the postpartum period was also examined as a moderator of these associations. Study design: We used a repeated-measures design, with self-report measures administered during pregnancy. Self-report and observational data were also collected at 2 months postpartum. Subjects: The study included a community sample of 64 pregnant women and their infants. Outcome measures: Participants completed measures assessing their early-life adversity and current depression/anxiety symptoms. At two months postpartum, mothers reported on their infant's temperament and participated in a parent-child interaction task designed to assess maternal sensitivity/responsiveness. Results and conclusions: Maternal adverse childhood experiences indirectly predicted poor self-regulation during early infancy via prenatal internalizing symptoms. Maternal sensitivity/responsiveness was also found to moderate the association between maternal adverse childhood experiences and certain aspects of infant regulatory capacity and positive affectivity at two months. This research has implications for mental health screening procedures during pregnancy and the development of early intervention programs. Highlights: Unknown how maternal early adversity relates to temperament. Maternal early adversity was associated with poor infant regulation via prenatal internalizing symptoms. More sensitive/responsive parenting was protective against the association with maternal early adversity. This research has implications for the development of early intervention programs.